Performance of Low-Height Railway Noise Barriers with Porous Materials - Lázaro, João (2022)
Rail transport is the most sustainable transportation mode, with the lowest energy consumption and carbon footprint. However, the noise induced by railway traffic in urban regions is a significant drawback and several reports point out the risks and the amount of people suffering from direct exposure to railway noise. One of the most used mitigation measures for railway noise is the implementation of noise barriers. Although they offer a significant reduction in noise levels, their height makes people feel enclosed. Therefore, in the case of railway infrastructure, the solution to the problem may lie in the use of barriers with a lower height placed close to the railway track. As the noise-forming mechanisms are mainly located at the track level, placing the barrier in a position close to the track allows mitigating rail noise without causing the problems identified above for the population in the vicinity. The purpose of this paper is to illustrate the development of a barrier solution to be used in a railway context through numerical modelling with the Boundary Element Method (BEM). The solutions developed were placed close to the track and have a low height. The geometry was defined so as to direct the energy back to the track to take advantage of the acoustic properties of the ballast. The addition of a porous granular material on the inner face of the barrier allows the control of reflections between the vehicle body and the barrier, increasing its acoustic efficiency. Finally, considering the most efficient solution, the insertion loss in a network of receivers located 10 m away from the track is analysed in order to study the noise reduction levels in a place where human receivers are usually located.